School culture and the quality of learning: The experience in Special Region of Yogyakarta - Buyung Surahman; Indra Pratama Putra Salmon (International Journal of Evaluation and Research in Education (IJERE), 2023)
Structural-based education is a significant challenge for elements of education in Indonesia. However, in the province of the Special Region of Yogyakarta, an alternative cultural approach strategy is applied during challenges from the structural model. This research uses the ethnographic method. The results showed that the quality of learning in research was based on structural learning strategies and value-based development efforts, which were then applied and applied in a learning culture (behavior, knowledge, and artefacts). These efforts are combined into a pattern of developing a learning culture and the pattern of gradual change, which also becomes a study. This research aims to bring up the concept of developing cultural learning strategies through values and practices while implementing structural educational policies. This study has limitations in the form of gaps in structural education problems that have not been confirmed, which are more inclined to the policy and political context, so the study requires a study pattern with a broader scope related to structural education problems that are still difficult to resolve, such as the development of equal access policies, education, and corruption.